1993
DOI: 10.1111/j.1442-9071.1993.tb00128.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiation hazards during cobalt 60 plaque therapy for choroidal melanoma

Abstract: Prompted by the concerns of the staff and patients, radiation hazards from Cobalt 60 (Co 60) plaque therapy for choroidal melanoma were recently assessed when two patients were concurrently treated at Christchurch Hospital. The risks from radiation to the attending medical staff, nursing personnel from the operating theatre and ward, and the patients' visitors were investigated.The radiation dose for all staff and visitors involved with the two patients was found to be well below the recommended weekly limits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The use of lower energy radioisotopes ( 125 I and 106 Ru) and gold-shielded radiation-blocking devices are two measures which have reduced the radiation exposure to surrounding ocular structures [11, 16, 25]. Investigators have also studied the use of adjuvant hyperthermia as a means of reducing the amount of radiation necessary for tumor control [26–30].…”
Section: Commentmentioning
confidence: 99%
“…The use of lower energy radioisotopes ( 125 I and 106 Ru) and gold-shielded radiation-blocking devices are two measures which have reduced the radiation exposure to surrounding ocular structures [11, 16, 25]. Investigators have also studied the use of adjuvant hyperthermia as a means of reducing the amount of radiation necessary for tumor control [26–30].…”
Section: Commentmentioning
confidence: 99%
“…Physical hazards in the general working environment that are also encountered in the hospital sector include temperature, illumination, noise, vibration, changes in atmospheric pressure, and ionizing and non-ionizing radiation [14-18]. A review of the international and Greek literature revealed the following physical hazards in the hospital working area: lighting, microclimate, noise, ionizing, and non ionizing radiation [19-22]. Lighting is a hazard that concerns all workers, especially during the night shift, in all hospital departments.…”
Section: Introductionmentioning
confidence: 99%
“…Physical hazards in the general working environment that are also encountered in the hospital environment include temperature, illumination, noise, vibration, slips, trips and falls, changes in atmospheric pressure, and ionizing and nonionizing radiation [5,[33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%